Service Value Assessment in Emerging Chain Restaurants in Nairobi Kenya - Nyaribo, Wycliffe Misuko; Owino, Edward; Wadawi, Joe Kibuye (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
Traditionally, Kenya’s restaurants have in the past largely depended on international tourists for the main stay of their business. With the earlier steady growth of Tourism in the 1980s, these restaurants registered very good business, also supported by the fact that there were only a handful of restaurants that could be considered as ‘tourist class’. However, tourist arrivals in Kenya began to face serious challenges in the 1990s. Simultaneously, more serious restaurant ventures made market entry, especially within the capital city of Nairobi. It has been acclaimed that the prices charged for local hospitality services have not worked well to support it. As this takes place, questions have been asked as to whether these new investments have introduced product and service quality that is worth the price that they charge for the same. It was against the argument that is developing above that this study carried out a value assessment amongst the emerging chain restaurants in Nairobi city. The study sought to establish the part played by restaurants in building destination competitiveness through quality service offer and value pricing. A series of chain restaurants operating in Nairobi were identified all together with the specific unit and outlets that they operate. The customers in these restaurants were conveniently sampled and interviewed to inform this study of their perceptual judgment of service and value. The data was then be analyzed and interpreted to establish the extent to which these customers approve of service and value and how this can influence Kenya’s destination competitiveness, both for domestic and international tourists. The assessment of customer expectation and perception resulted in a four factor construct. An assessment of service quality led to the identification of the critical latent variables that leads to customer attraction and satisfaction in restaurants. An evaluation of prices charged indicated that price is a critical component in value assessment amongst customers.